Determination of Motor Vehicle Insurance Risk Premium - Mustofa, Pramesti Melyna; Muhammad, Hubbi (Program Studi Matematika, Universitas Tadulako, 2024)
Insurance is a service that transfers specific financial loss risks to an insurer in exchange for a fixed payment, known as a premium. The determination of this premium is tailored to the policyholder's level of risk. In this study, the calculation of premium risks is conducted by analyzing the frequency and size of claims related to motor vehicle insurance. The analysis focuses on different types of vehicles and their associated risks, as well as variations in vehicle usage based on geographical regions. This approach enables insurers to better understand risk patterns and predict potential future losses, ensuring accurate premium determination